If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2r + 8) = 4(3r + -9) Reorder the terms: 3(8 + 2r) = 4(3r + -9) (8 * 3 + 2r * 3) = 4(3r + -9) (24 + 6r) = 4(3r + -9) Reorder the terms: 24 + 6r = 4(-9 + 3r) 24 + 6r = (-9 * 4 + 3r * 4) 24 + 6r = (-36 + 12r) Solving 24 + 6r = -36 + 12r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-12r' to each side of the equation. 24 + 6r + -12r = -36 + 12r + -12r Combine like terms: 6r + -12r = -6r 24 + -6r = -36 + 12r + -12r Combine like terms: 12r + -12r = 0 24 + -6r = -36 + 0 24 + -6r = -36 Add '-24' to each side of the equation. 24 + -24 + -6r = -36 + -24 Combine like terms: 24 + -24 = 0 0 + -6r = -36 + -24 -6r = -36 + -24 Combine like terms: -36 + -24 = -60 -6r = -60 Divide each side by '-6'. r = 10 Simplifying r = 10
| 2x+5-3x+8=7 | | 4x^2-40-12=0 | | 11(3y-2)=5(6y-5) | | 8x^2+22x+5=0 | | 6x+1.2=9x+2 | | 11(3y-2)=5(6y+5) | | 42x=84 | | 189=-7(3a-3) | | 22=5x+2 | | 5(2n-5)=4n-1 | | 28x=84 | | 8(-6x-7)-3x=-11-6x | | 50x=1500 | | 14x-6x-6x=16 | | 9x-30x=45 | | 20X^2-15x+35=0 | | 14x+12=24 | | 2x+3x= | | -3b+24=-4(6b-6) | | 4x-6=12x+8x | | 3(2+4n)-2(5n-3)=25 | | 2x+2y=19 | | 7(r+2)=4(-r) | | 8x+3x+5x=-256 | | x^2+6x=40 | | -y+48y-203=0 | | 2y^2-6y-20= | | -20+5k=3(4+3k) | | 22(g-1)=2g+g | | 4+.666n=3 | | k-14=-6 | | 8x=4(2x+2) |